Google Classroom: A Learning Media In Increasing Students' Motivation - M Daud Batubara; Zohri Hamdani; Mark Philip Paderan (ILIN Institute Makassar, 2021)
The objective of this study is to know the effect google classroom as learning platform in increasing students’ learning motivation in non-formal education subject of students’ Early Childhood Education programs during the first semester STAIN Mandailing Natal 2020/2021. This study is an experimental research with descriptive analysis. The population of this study was 128 students and there are 25 students as respondents in the cluster class. Pre-test and Post-test were used as techniques in collecting data. To analyze the data, the researcehrs used SPSS 16. The result of this study showed that the mean of pre-test was 47.692 and Post-test was 76.154 which can be concluded that there is an increase in the students’ learning motivation in experimental group using Google Classroom